2006
DOI: 10.1086/499411
|View full text |Cite
|
Sign up to set email alerts
|

Polarity and Temporality of High-Resolution Y-Chromosome Distributions in India Identify Both Indigenous and Exogenous Expansions and Reveal Minor Genetic Influence of Central Asian Pastoralists

Abstract: Although considerable cultural impact on social hierarchy and language in South Asia is attributable to the arrival of nomadic Central Asian pastoralists, genetic data (mitochondrial and Y chromosomal) have yielded dramatically conflicting inferences on the genetic origins of tribes and castes of South Asia. We sought to resolve this conflict, using high-resolution data on 69 informative Y-chromosome binary markers and 10 microsatellite markers from a large set of geographically, socially, and linguistically r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

28
459
7
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 367 publications
(495 citation statements)
references
References 53 publications
28
459
7
1
Order By: Relevance
“…Our recent study on Y-chromosomal diversity in the Himalayan populations of Nepal and Tibet revealed high frequencies of East Asian-specific haplogroup O3a5-M134, congruent with earlier reports on TB groups, 4,7,8,9 suggesting a common ancestry for this language subfamily. 1 This investigation also revealed elevated levels of South Asian-derived Y-haplogroup R1a1-M198 in the Nepalese populations of Kathmandu and Newar, indicating significant genetic influences from the Indian subcontinent, whereas the Himalayas served as a barrier to gene flow from the south into the Tibetan plateau.…”
Section: Introductionsupporting
confidence: 91%
“…Our recent study on Y-chromosomal diversity in the Himalayan populations of Nepal and Tibet revealed high frequencies of East Asian-specific haplogroup O3a5-M134, congruent with earlier reports on TB groups, 4,7,8,9 suggesting a common ancestry for this language subfamily. 1 This investigation also revealed elevated levels of South Asian-derived Y-haplogroup R1a1-M198 in the Nepalese populations of Kathmandu and Newar, indicating significant genetic influences from the Indian subcontinent, whereas the Himalayas served as a barrier to gene flow from the south into the Tibetan plateau.…”
Section: Introductionsupporting
confidence: 91%
“…6 Tribals constitute 8.08% of the total population 7,8 and the majority of them speak languages belonging to AA, DR and TB families; 8 also, most of them are believed to be autochthones of India. 9 On the contrary, most of the contemporary non-tribal populations belong to Hindu religion and speak languages of IE and DR descent. In addition, there are several other religious communities contributing a fraction to the total Indian population structure.…”
Section: Introductionmentioning
confidence: 99%
“…11 The co-existence of IE tribes and DR castes indicates a complex historical interaction and suggests no 'one to one correlation' between language and this social organization. 12 In spite of the consensus on the relatively uniform maternal gene pool of Indian populations and the large efforts through many philological, 13,14 archaeological 15,16 and recent molecular genetic approaches to elucidate rival models, 6,7,9,11,12,[17][18][19][20][21] the history and concepts of the origin of the caste system are still controversial and unclear. The competing main models (the first of them based on shared IE languages) suggest that contemporary Hindu Indians are descendants of primarily West Eurasians who migrated from the Near east, Antolia and the Caucasus 3000-8000 years ago, 13,14 which has been supported by the demic diffusion model 1,22 and validated by molecular genetic data.…”
Section: Introductionmentioning
confidence: 99%
“…[61][62][63][64][65][66] This study throws light on religious grounds for clear understanding of genetic diversity patterns in Indian Muslims. According to historians and anthropologists, the augmentation of Islamic faith in India could be through two discrete ways (i) military invasions that flourished Muslim kingdoms and subsequent migration of mercenaries, businessmen and political emissaries from Middle Eastern countries, Iran and Arabia followed by admixture with the local population; (ii) cultural diffusion as a result of absorption and dominance that resulted in a sizeable population embracing Islam.…”
Section: Discussionmentioning
confidence: 99%